Livingstone's 'lives' : A metabiography of a Victorian icon - Livingstone, Justin D. (Book collections on Project MUSE., 2015)
This study interrogates the heterogeneous nature of Livingstone's legacy and explores the plurality of identities that he has posthumously acquired. Investigating Livingstone's own self-staging, his Victorian commemoration, his imperialist and Scottish reputations, and his afterlife in postcolonial fiction and drama, it offers the first full exploration of his many incarnations over a lengthy chronological period.